Administration of public sector enterprises: changing trends since independence - Verma, Sandeep (ed.); Batra, Satish Kumar (ed.) (Jaipur, 2008)
The book is about a number of issues related to PSU management and to the administration of industrial development, such as the nature of the debate regarding state enterprises, the changing contours of public policy and the ideas that have shaped and influenced political and economic approaches in these spheres from independence to the present day.
Keywords: Public sector enterprises-Administration